Conceptualising supper as an institution : what are the social issues that embed and shape this institution in Singapore? - Koh, Si Hui. (2009)
Supper goes beyond consuming food and beverage late at night. It is seemingly an activity that Singaporeans engage in for social reasons rather than just the mere satisfaction of their hunger. In some sense, eating supper forms a characteristic and significant feature in the life of Singaporeans. In this research paper, I propose a conceptual framework for studying supper as an institution. I will explore how supper is accomplished (supper practices) by Singaporeans, how this gives shape to the institution, and how the institution is reproduced by such practices. Implicated within the practices of supper are other social issues which I will expound on in my analysis. Given that this institution is embedded in Singapore society, the interactions between supper and other institutions lend themselves to examination. And, if supper is indeed institutionalized in Singapore, what are the implications for those who do not participate in this institution?